PEMENUHAN NAFKAH SUAMI ISTRI YANG MASIH MENEMPUH PENDIDIKAN TINGGI PRESPEKTIF KOMPILASI HUKUM ISLAM DAN PEMIKIRAN IMAM SYAFI’I - Mukhotib, Zainal; Rahmania Kusumawati, Ita (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2023)
A husband and wife who are pursuing their undergraduate degree not only have to divide their time for studying but also have an obligation to fulfill their family's needs. This will certainly affect their economy. This research focuses on fulfilling the wife's needs and the husband's strategy to fulfill those needs while still studying. This research uses a descriptive normative qualitative method and data collection methods in the form of interviews with several students and reading classical literature by Imam Syafi'i. The researcher took samples from three campuses, namely STAIDA, STAIM, and IAIDIPO, whose student backgrounds are heterogeneous. After the data was collected, the author analyzed the practice of fulfilling needs in the field with the rules in the Compilation of Islamic Law and the thoughts of Imam Syafi'i. There are two results from this study: first, the fulfillment of the needs of husband and wife who are pursuing higher education is done in two ways, one by determining the nominal amount of the wife's needs. Second, fulfillment without determining the nominal amount of the wife's needs. The next result, based on the rules in the Compilation of Islamic Law and the thoughts of Imam Syafi'i, the practice of fulfilling the needs of husband and wife who are pursuing higher education can be classified into two groups. One is the fulfillment of the wife's needs that already comply with the rules in the Compilation of Islamic Law and the thoughts of Imam Syafi'i and have been maximally fulfilled. Two is the fulfillment of needs that do not comply with the rules in the Compilation of Islamic Law and the thoughts of Imam Syafi'i.